PENGARUH PEMBAGIAN KERJA TERHADAP EFEKTIFITAS KERJA PEGAWAI PADA SEKRETARIAT BADAN GEOLOGI BANDUNG - AI NUNUNG AI NUNUNG (POLITEKNIK PIKSI GANESHA, 2019)
The study was based on the central issue, namely the Employee Work Effectiveness is thought to be caused by low-yet-idimensi Dimens exercise of an optimal division of work. It is not thought to be caused by the exercise of the dimensions of the Division of Labour as a whole Sekretariat badan Geologi Bandung. The approach in this study on the Division of Employment and Employee Work Effectiveness seen in the context of Public Administration by using the dimensions of Division of Labour.The research method used, the survey method deskriptip explanative. This method is used to explain social phenomena in this case is used to explain social phenomena in terms that are used to investigate the influence of Division of Labour (independent variabel) is symbolized by the X on Employee Work Effectiveness (bound variabel) which is symbolized by Y. This study uses quantitative analysis through the use of Path Analysis Method (Analysis Part) which dimaksudka nTo find out the amount of division of labor is a variabel effect on employees on the Work Effectiveness Sekretariat Badan Geologi Bandung, either simultaneously or partially.